2010
DOI: 10.1016/j.virol.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gene expression profile of human bocavirus

Abstract: We have generated a quantitative transcription profile of human bocavirus type 1 (HBoV1) by transfecting a nearly full-length clone in human lung epithelial A549 cells as well as in a replication competent system in 293 cells. The overall transcription profile of HBoV1 is similar to that of two other members of genus Bocavirus, minute virus of canines and bovine parvovirus 1. In particular, a spliced NS1-transcript that was not recognized previously expressed the large non-structural protein NS1 at approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(166 citation statements)
references
References 60 publications
13
146
2
5
Order By: Relevance
“…A previous report (53) and the results of this study (Fig. 6B, 6C) showed that NP1 mostly located in the nucleus.…”
Section: Hbov Np1 Interacts With Irf-3supporting
confidence: 83%
See 2 more Smart Citations
“…A previous report (53) and the results of this study (Fig. 6B, 6C) showed that NP1 mostly located in the nucleus.…”
Section: Hbov Np1 Interacts With Irf-3supporting
confidence: 83%
“…Although the overexpression of NP1 and NS1 significantly inhibited IFN-b production, research on the HBoV gene-expression profile showed that NP1 was much more abundant than was NS1 (53). Therefore, we focused on NP1 in the following experiment.…”
Section: Hbov Np1 Inhibits Both Sev-and Poly(da-dt)-stimulated Ifn-b mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report, human airway epithelia infected with HBoV were revealed to result in cilia loss and airway epithelial cell hypertrophy; however this was not associated with apoptotic or necrotic cell death (23). Similarly, a previous study demonstrated that HBoV nonstructural protein failed to cause cell death (5). However, in the present study, we demonstrated that HBoV recombination expressing vector (pWHL-1) induced proliferation inhibition, apoptosis and autophagy in HBECs.…”
Section: Discussionsupporting
confidence: 46%
“…HBoV encodes three nonstructural proteins including: NP1, NS1 and NS1-70, in addition to two structural proteins, VP1 and VP2. HBoV NP1 is a nuclear protein, which has an important role in the DNA replication process of HBoV within the nuclei of infected cells (5,6). It has been reported that NP1 is able to cause cell cycle arrest at G2/M phase followed by apoptosis, via the mitochondrion pathway in HeLa cells (7).…”
Section: Introductionmentioning
confidence: 99%